ANTIFUNGAL ACTIVITIES OF MAULI BANANA STEM AND BASIL LEAVES EXTRACT MIXTURE AGAINST Candida albicans - Nor Kamalia; Maharani Laillyza Apriasari; Yusrinie Wasiaturrahmah (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACTBackground: Mauli banana stem and basil leaves are natural ingredients that have the potential to be used as a treatment for Candida albicans infections. The methanol extract of mauli banana stem with 25% concentration is merely fungistatic which is still not capable to induce fungicidal effect, while the 100% concentration is known to be less effective than 0.2% chlorhexidine gluconate. Adding basil leaves extract to mauli banana stem extract is expected to increase antifungal activities against Candida albicans. Purpose: to analyze the antifungal activity of mauli banana stem and basil leaves extract mixture with concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100% against Candida albicans by dilution method. Method: This research used a true experimental method with a pretest–posttest control group design consisting of 11 treatments to obtain Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Result: The 10% concentration was identified as the Minimum Inhibitory Concentration (MIC), and no concentration could be classified as the Minimum Bactericidal Concentration (MBC) because all treatment group still exhibited Candida albicans growth on the SDA medium. Conclusion: Mauli banana stem and basil leaves extract mixture has an MIC value of 10% and does not demonstrate any value for the MBC. Keywords: Basil leaf, Candida albicans, Mauli banana stem, MBC, MIC